Growth and Anatomical Parameters of Adventitious Roots Formed on Mung Bean Hypocotyls Are Correlated with Galactoglucomannan Oligosaccharides Structure - K. Kollárová; I. Zelko; M. Henselová; P. Capek; D. Lišková (The Scientific World Journal)
The effect of galactoglucomannan oligosaccharides (GGMOs) compared with chemically modified oligosaccharides, GGMOs-g (with reduced number of D-galactose side chains) and GGMOs-r (with reduced reducing ends) on mung bean (Vigna radiata (L.) Wilczek) adventitious roots formation, elongation, and anatomical structure have been studied. All types of oligosaccharides influenced adventitious root formation in the same way: stimulation in the absence of exogenous auxin and inhibition in the presence of exogenous auxin. Both reactions are probably related with the presence/content of endogenous auxin in plant cuttings. However, the adventitious root length was inhibited by GGMOs both in the absence as well as in the presence of auxin (IBA or NAA), while GGMOs-g inhibition was significantly weaker compared with GGMOs. GGMOs-r were without significant difference on both processes, compared with GGMOs. GGMOs affected not only the adventitious root length but also their anatomy in dependence on the combination with certain type of auxin. The oligosaccharides influenced cortical cells division, which was reflected in the cortex area and in the root diameter. All processes followed were dependent on oligosaccharides chemical structure. The results suggest also that GGM-derived oligosaccharides may play an important role in adventitious roots elongation but not in their formation.